Systematic Literature Review of Scientific Approaches in Islamic Education Pedagogy - Hafidhah Syafni; Rahmania Auriel Zaeni; Muhammad Fahrudin Nur (ASSUNNAH PRESS, 2025)
The scientific approach is increasingly popular in Islamic Religious Education (PAI) learning, and it has been widely used in the learning process with a particular focus and material. This study aims to systematically summarise and analyse several studies on the implementation of the scientific approach in PAI learning, then determine the impact of its implementation on improving students' learning achievement and interest in learning, as well as identify challenges and opportunities faced in the future. The research method used in this paper is a systematic literature review approach, in which researchers collected 20 scientific articles from reputable journals obtained through Google Scholar, with selection criteria including topic relevance and research results that can provide insight into the scientific approach in the past 5 years. The results showed that the implementation of the scientific approach was proven to improve students' critical thinking skills, learning interest and academic achievement. It is also able to improve students' understanding of the subject matter as well as forming better character and critical thinking skills. Nevertheless, its implementation certainly faces challenges, especially related to the availability of relevant learning resources and teachers' skills in using the scientific approach. On the other hand, there are also great opportunities, such as the utilisation of technological media and cross-disciplinary collaboration, which can improve learning effectiveness.